Technical efficiency of vegetable farming among partner farmers in Kota Besi Hulu Village, Kota Besi District, East Kotawaringin Regency - Santosa, Iwan; Manihuruk, Ekamonika (Universitas Musamus, Merauke, Papua, 2025)
One of the vegetable centers in East Waringin Regency City is District. Iron City. This area was developed as a production center because the land area is quite high compared to other areas in East Kotawaringin Regency. However, currently several vegetable production commodities continue to fluctuate from year to year. The aim of this research is to analyze the technical efficiency of partner vegetable farmers, in increasing productivity. This research will use a holistic and empirical approach. The population of this study consisted of 80 farmers who were registered as active partner members. The entire population was sampled in this study. Descriptive analysis was used to identify the socio-economic conditions of partner farmers and explain farming performance in Kota Besi District. Meanwhile, in analyzing technical efficiency, quantitative analysis is used. The results obtained were that the technical efficiency of partner vegetable farmers in Kota Besi Subdistrict, Kota Besi district, mustard greens was 87.13, red chilies were 83.15 and beans were 72.19. Increased production can still be done in the research area.